2000
DOI: 10.1159/000014242
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and 17-Hydroxyprogesterone Levels in Saliva of Healthy Neonates

Abstract: The measurement of cortisol and 17-hydroxyprogesterone (17-OHP) in saliva has become a reliable tool for both the scientist and the clinician for studying adrenal cortical function in the adult and the older child. We have now established in parallel normative data for salivary cortisol and 17-OHP levels in healthy neonates. We have asked whether or not there is a circadian rhythm of cortisol and 17-OHP saliva levels in neonates. Furthermore, we have asked whether salivary hormone levels correlated with auxolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Our mean data for cortisol and 17OHP also fit with previously reported data in neonates (33 ), although the variation in our values was smaller. One study (33 ) reported wide ranges for cortisol (up to 166 nmol/L) and 17OHP (Ͼ5160 pmol/L), and it is possible that the extreme morning values for cortisol and 17OHP may partially reflect a stress response to the Salivette used. From our own experience, the Salivette is not suitable for use in newborns because of the large size of the cotton swab (diameter, 1.3 cm; length, 3.5 cm).…”
supporting
confidence: 90%
“…Our mean data for cortisol and 17OHP also fit with previously reported data in neonates (33 ), although the variation in our values was smaller. One study (33 ) reported wide ranges for cortisol (up to 166 nmol/L) and 17OHP (Ͼ5160 pmol/L), and it is possible that the extreme morning values for cortisol and 17OHP may partially reflect a stress response to the Salivette used. From our own experience, the Salivette is not suitable for use in newborns because of the large size of the cotton swab (diameter, 1.3 cm; length, 3.5 cm).…”
supporting
confidence: 90%
“…The range of salivary cortisol levels were within the range previously reported by Klug et al (2000) for newly born full‐term infants between 25 and 55 hours postbirth (0.24–6 μg/dl). There were no significant differences in cortisol level among the three groups at baseline.…”
Section: Resultssupporting
confidence: 91%
“…The circadian rhythm of cortisol becomes established in term infants between 8 and 12 postnatal weeks (Castro et al, 2000; Klug et al, 2000). However, to control for any potential circadian patterns, the intervention and cortisol sampling were conducted at the same time of day over the course of the research (between 10 a.m. and 1 p.m.).…”
Section: Methodsmentioning
confidence: 99%
“…The swab was left in the neonates' mouth for 5 minutes. This procedure did not cause any distress 14. None of the neonates showed discomfortable signs during saliva collection.…”
Section: Methodsmentioning
confidence: 83%